Ensayo y error restringido y orientado: Esquema de una lógica del descubrimiento científico - Cassini, Alejandro (Análisis Filosófico, 1996)
This paper outlines a logic of scientific discovery. First, it argues that discovery rules must be general and able to guide the search for novel hypotheses. Then, it criticizes Zahars' deductivist logic of discovery, but accepts his idea of general heuristics principles. It shows that these principies are compatible with a complex version of retroduction. An historical case -the discovery of neutrino- is examined applying this approach. Finally, it concludes that this logic of discovery culminates in a restricted and directed method of trial and error.